Assessment of a high‐SNR chemical‐shift‐encoded MRI with complex reconstruction for proton density fat fraction (PDFF) estimation overall and in the low‐fat range. Issue 1 (29th April 2018) - Park, Charlie C.; Hooker, Catherine; Hooker, Jonathan C.; Bass, Emily; Haufe, William; Schlein, Alexandra; Covarrubias, Yesenia; Heba, Elhamy; Bydder, Mark; Wolfson, Tanya; Gamst, Anthony; Loomba, Rohit; et al.
Abstract : Background: Improving the signal‐to‐noise ratio (SNR) of chemical‐shift‐encoded MRI acquisition with complex reconstruction (MRI‐C) may improve the accuracy and precision of noninvasive proton density fat fraction (PDFF) quantification in patients with hepatic steatosis. Purpose: To assess the accuracy of high SNR (Hi‐SNR) MRI‐C versus standard MRI‐C acquisition to estimate hepatic PDFF in adult and pediatric nonalcoholic fatty liver disease (NAFLD) using an MR spectroscopy (MRS) sequence as the reference standard. Study Type: Prospective. Population/Subjects: In all, 231 adult and pediatric patients with known or suspected NAFLD. Field Strength/Sequence: PDFF estimated at 3T by three MR techniques: standard MRI‐C; a Hi‐SNR MRI‐C variant with increased slice thickness, decreased matrix size, and no parallel imaging; and MRS (reference standard). Assessment: MRI‐PDFF was measured by image analysts using a region of interest coregistered with the MRS‐PDFF voxel. Statistical Tests: Linear regression analyses were used to assess accuracy and precision of MRI‐estimated PDFF for MRS‐PDFF as a function of MRI‐PDFF using the standard and Hi‐SNR MRI‐C for all patients and for patients with MRS‐PDFF <10%. Results: In all, 271 exams from 231 patients were included (mean MRS‐PDFF: 12.6% [SD: 10.4]; range: 0.9–41.9). High agreement between MRI‐PDFF and MRS‐PDFF was demonstrated across the overall range of PDFF, with a regression slope of 1.035 for the standard MRI‐C and 1.008 for Hi‐SNR MRI‐C. Hi‐SNR MRI‐C, compared to standard MRI‐C, provided small but statistically significant improvements in the slope (respectively, 1.008 vs. 1.035, P  = 0.004) and mean bias (0.412 vs. 0.673, P  < 0.0001) overall. In the low‐fat patients only, Hi‐SNR MRI‐C provided improvements in the slope (1.058 vs. 1.190, P  = 0.002), mean bias (0.168 vs. 0.368, P  = 0.007), intercept (−0.153 vs. −0.796, P  < 0.0001), and borderline improvement in the R 2 (0.888 vs. 0.813, P  = 0.01). Data Conclusion: Compared to standard MRI‐C, Hi‐SNR MRI‐C provides slightly higher MRI‐PDFF estimation accuracy across the overall range of PDFF and improves both accuracy and precision in the low PDFF range. Level of Evidence: 1 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2019;49:229–238.